Magnetohydrodynamic flow and heat transfer of ferrofluid over a flat plate, circular cylinder and sphere - Siti Hanani, Mat Yasin (2025)
Ferrofluid exhibits features of magnetism under the influence of a magnetic field in one fluid medium. The benefits of ferrofluid are lost without the magnetic field. The spontaneous magnetization behaviour of ferrofluid in the presence of a magnetic field provides a remarkable advantage to the thermal transfer. Therefore, the development and sustainability of ferrofluid utilisation for broad industries are still in progress since the ferrofluid invention to capture the innovation demand. Consequently, this thesis is dedicated to investigating the ferrofluid flow and convective heat transfer over three different geometrical surfaces through a theoretical study. Due to a magnetic field, the effect of magnetohydrodynamic flow must be observed to understand the characteristics of ferrofluid. Besides, the exposure from thermal radiation to the magnetohydrodynamic flow acts as an added attribute to illustrate the practical configurations of ferrofluid flow and the convective heat transfer mechanism on a surface. The interaction between ferrofluid motion and the heated surface can be measured by the boundary layer theory. The modified mathematical model in the form of dimensional nonlinear partial differential equations is derived to represent the flow regime and heat transfer occurrence over all three geometrical surfaces (flat plate, horizontal circular cylinder and sphere). Next, the governing equations are simplified to nonlinear ordinary/partial differential equations by using appropriate similarity/non-similarity transformation in order to reduce the complexity. Subsequently, these equations are solved numerically by using the Keller-box method, which is implemented in MATLAB software. The influences of ferroparticles volume fraction, magnetic parameter, thermal radiation parameter and mixed convection parameter are examined on velocity profile, temperature profile, reduced skin friction coefficient and reduced Nusselt number. The results found that the applied magnetic field creates a significant contribution to shear stress represented by the reduced skin friction coefficient and convective heat transfer represented by the reduced Nusselt number over all three geometrical surfaces. Concurrent with the boundary layer separation phenomena on the horizontal circular cylinder and sphere surfaces, the flow separation occurs in the presence of increasing magnetic field strength. Different outcomes to the emitted effect from the thermal radiation are shown through the presence of thermal radiation only works to the heat transfer performance but not shear stress. Meanwhile, the ferroparticles volume fraction parameter plays an important role in this study because the fluid viscosity changes when that parameter value elevates. Hence, the viscosity rate of ferrofluid hugely impacts the results of velocity and temperature profiles when flowing over the three geometrical surfaces. The results for all problems showed that the contribution of applied parameters is stimulated by buoyancy force and Lorentz force. The interplay between buoyancy force and Lorentz force induces certain flow patterns that can be used to control flow behaviour in response to external stimuli. This phenomenon provides critical insights into ferrofluid flow on the surfaces that help researchers investigate the same problem in real applications and verify the experimental study.